Tongxinluo May Alleviate Inflammation and Improve the Stability of Atherosclerotic Plaques by Changing the Intestinal Flora - Qi, Yan; Liu, Wenzhao; Yan, Xuefang; Zhang, Chen; Zhang, Chunmei; Liu, Lingxin; Zheng, Xuehui; Suo, Mengying; Ti, Yun; Ni, Mei; Zhang, Meng; Bu, Peili (Frontiers in Pharmacology, 2022)
Intestinal flora plays an important role in atherosclerosis. Tongxinluo, as a multi-target Chinese medicine to improve atherosclerosis, whether it can improve atherosclerosis by affecting the intestinal flora is worth exploring. We established a vulnerable plaque model of atherosclerosis in New Zealand white rabbits by high cholesterol diet and balloon injury (HCB), and performed Tongxinluo intervention. We detected the level of inflammation by immunohistochemistry, Western Blot, and ELISA, analyzed plaque characteristics by calculating the vulnerability index, and analyzed the changes of gut microbiota and metabolites by 16S rRNA gene sequencing and untargeted metabolomic sequencing. The results showed that Tongxinluo intervention improved plaque stability, reduced inflammatory response, inhibited NLRP3 inflammatory pathway, increased the relative abundance of beneficial bacteria such as Alistipes which reduced by HCB, and increased the content of beneficial metabolites such as trans-ferulic acid in feces. Through correlation analysis, we found that some metabolites were significantly correlated with some bacteria and some inflammatory factors. In particular, the metabolite trans-ferulic acid was also significantly positively correlated with plaque stability. Our further studies showed that trans-ferulic acid could also inhibit the NLRP3 inflammatory pathway. In conclusion, Tongxinluo can improve plaque stability and reduce inflammation in atherosclerotic rabbits, which may be achieved by modulating intestinal flora and intestinal metabolism. Our study provides new views for the role of Tongxinluo in improving atherosclerotic vulnerable plaque, which has important clinical significance.